KONSTRUKSI INFORMASI POLITIK (STUDI KASUS PADA MASYARAKAT KOTA CIMAHI PASCA PENETAPAN CALON WALIKOTA DAN WAKIL WALIKOTA DALAM PILKADA SERENTAK ) - Adiyana Slamet (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The consolidation of local democracy will be realized well if the political information provided by the electoral institutions and political institution through political communication can encourage people to get a 'nutrition' receive political information, so they can learn about politics. Political information in simultaneosly election is part of candidate “candidates pair” a Mayor Cimahi City can do political communication for competing to provide on political information about prospective policy choice that will be submitter later. When the political information of the citizen is fulfilled, the citizen can choose with a large responsibility and rationally to choose leader in their area, based on considerations that the common benefit of the people themselves. In 2017 is a political year for 101 regions that held the head simultaneous elections (Pilkada) throughout in Indonesia. There are 7 Provinces, 76 District and 18 Cities that participate in the simultaneous elections. One of the 18 cities that held the elections was Cimahi City. Cimahi City has a permanent voter list of 375,722 people who use its sovereignty to elect a Mayor candidate who will lead the region for the next 5 years. In the party of democracy, it is fundamental that political information becomes a reinforcement in political cognition that will be implemented in the space of political participation itself. Political education is an obligation for political organizers, especially for the General Election Commision (KPU) Cimahi City and Political Parties to provide political information to the public.